p75NTR promotes tooth rhythmic mineralization via upregulation of BMAL1/CLOCK - Xie, Bo; Yuan, Hongyan; Zou, Xuqiang; Lu, Mingjie; Zhang, Yixin; Xu, Dan; Peng, Xuelian; Wang, Di; Zhao, Manzhu; Wen, Xiujie (Frontiers in Cell and Developmental Biology, 2023)
The circadian clock plays a critical role in dentomaxillofacial development. Tooth biomineralization is characterized by the circadian clock; however, the mechanisms underlying the coordination of circadian rhythms with tooth development and biomineralization remain unclear. The p75 neurotrophin receptor (p75NTR) is a clock factor that regulates the oscillatory components of the circadian rhythm. This study aims to investigate the impact of p75NTR on the rhythmic mineralization of teeth and elucidate its underlying molecular mechanisms. We generated p75NTR knockout mice to examine the effects of p75NTR deficiency on tooth mineralization. Ectomesenchymal stem cells (EMSCs), derived from mouse tooth germs, were used for in vitro experiments. Results showed a reduction in tooth mineral density and daily mineralization rate in p75NTR knockout mice. Deletion of p75NTR decreased the expression of DMP1, DSPP, RUNX2, and ALP in tooth germ. Odontogenic differentiation and mineralization of EMSCs were activated by p75NTR. Histological results demonstrated predominant detection of p75NTR protein in odontoblasts and stratum intermedium cells during rapid formation phases of dental hard tissue. The mRNA expression of p75NTR exhibited circadian variations in tooth germs and EMSCs, consistent with the expression patterns of the core clock genes Bmal1 and Clock. The upregulation of BMAL1/CLOCK expression by p75NTR positively regulated the mineralization ability of EMSCs, whereas BMAL1 and CLOCK exerted a negative feedback regulation on p75NTR by inhibiting its promoter activity. Our findings suggest that p75NTR is necessary to maintain normal tooth biomineralization. Odontogenic differentiation and mineralization of EMSCs is regulated by the p75NTR-BMAL1/CLOCK signaling axis. These findings offer valuable insights into the associations between circadian rhythms, tooth development, and biomineralization.